2018
DOI: 10.1177/1533033818809051
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Immobilization Mask Molding Through the Use of 3D-Printed Head Models

Abstract: Purpose:To evaluate the feasibility of a workflow free of a simulation appointment using three-dimensional-printed heads and custom immobilization devices.Materials and Methods:Simulation computed tomography scans of 11 patients who received radiotherapy for brain tumors were used to create three-dimensional printable models of the patients’ heads and neck rests. The models were three-dimensional-printed using fused deposition modeling and reassembled. Then, thermoplastic immobilization masks were molded onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Data captured from the literature also reveals that 78% (n = 14) of studies used 3D printing to fabricate the end-use immobiliser or headrest, while 11% (n = 2) used 3D printing to produce a replica of a head over which a traditional thermoformed mask immobiliser was created [32,38], and one study used 3D printing to produce several immobilisers as well as a head for thermoforming a traditional mask over [10]. Six of the studies examined the accuracy of the 3D printed immobilisers, with four studies finding a good level of accuracy in face masks on human volunteers [29][30][31]34], and one study finding a high degree of accuracy compared to the initial CAD model [11].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data captured from the literature also reveals that 78% (n = 14) of studies used 3D printing to fabricate the end-use immobiliser or headrest, while 11% (n = 2) used 3D printing to produce a replica of a head over which a traditional thermoformed mask immobiliser was created [32,38], and one study used 3D printing to produce several immobilisers as well as a head for thermoforming a traditional mask over [10]. Six of the studies examined the accuracy of the 3D printed immobilisers, with four studies finding a good level of accuracy in face masks on human volunteers [29][30][31]34], and one study finding a high degree of accuracy compared to the initial CAD model [11].…”
Section: Resultsmentioning
confidence: 99%
“…Summarising the literature on 3D printed immobilisation devices, the identified advantages of the technology included: improved patient comfort [9,29,34,37], reduced patient visits to a clinic [32,35,41], elimination of the stressful thermoforming process for face masks [29,31,34,40], high accuracy and tolerance to the patient [11,[29][30][31]34], repeatable positional accuracy [29,33,34,36,39,42], less damage to surrounding healthy tissue [40,42], similar beam attenuation properties to traditional polymer masks [10,11,33,39] and the opportunity to consider additional features to improve fit or patient engagement [37,38]. Disadvantages that were identified in the literature included: the potential for the 3D printing process to negatively influence the material behaviour of a device [30], inaccuracies due to conversion of scan data (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pham et al used 3D-printed head models from patients' CT scans to fabricate thermoplastic masks before a patient's simulation. 5 Haefer et al and Sato et al demonstrated the feasibility of using 3D-printed masks for immobilization in linac-based radiotherapy of head and neck cancers. 6,7 The purpose of this study was to design and validate a 3Dprinted headrest for patient immobilization for frameless Gamma Knife SRS treatments.…”
Section: Introductionmentioning
confidence: 99%